Glacial Lake Outburst Floods (GLOFs) in the Nepal Himalayas: Recent events, urgent response, and global actions for cryospheric science (Journal of Tourism and Himalayan Adventures, 2025)
The Nepal Himalayas are experiencing an unprecedented rise in cryosphere-induced hazards, especially Glacial Lake Outburst Floods (GLOFs), as a result of rapid glacial retreat driven by anthropogenic climate change. Between 2024 and 2025, three major GLOF events, the Birendra Lake flood (April 2024), the Thame GLOF (August 2024), and the Limi Valley GLOF (May 2025) demonstrated the escalating frequency and intensity of such disasters. These events pose serious threats not only to vulnerable mountain communities and local biodiversity but also to globally significant mountain ecosystems, including the Sagarmatha National Park, a UNESCO World Heritage Site. This paper provides a comprehensive analysis of these recent events, identifies critical gaps in monitoring, preparedness, and response, and highlights the urgent need for improved integration of cryospheric science with local adaptation and international cooperation. By linking Nepal’s experience with global frameworks like the International Year of Glacier Preservation (IYGP-2025) and the UN Decade of Action for Cryospheric Sciences (2025–2034), this study contributes new insights into the pathways for achieving equitable, science-driven, and community-based climate resilience.